Pinpointing Poverty in the Slovak Republic - World Bank Group (World Bank, Washington, DC, 2016)
The EC and the World Bank, in cooperation with individual EU member states, have developed a set of high-resolution poverty maps. The greater geographical disaggregation of the new poverty maps reveals which parts of these larger regions have particularly high rates of poverty and require greater attention in poverty reduction programs.